Managing conflicts through strength of identity - Claude-Hélène Mayer (Management Revue, 2009)
Identity, in management sciences, comprises a newly popular research topic. This article assesses identity aspects based on intra- and inter-personal constructs, as well as conflict and the management thereof in a selected international automotive organization in South Africa. It introduces the recent theoretical research and presents selected qualitative research findings from a case study. The aim of this article, therefore, is to investigate managerial identity aspects, as well as their strengthening and weakening impacts with regard to conflict and its management. According to the research findings, managers construct identity and conflict which are simultaneously connected to strengthening and weakening internal and external impacts. These impacts influence the way in which managers resolve organizational conflicts and contribute, either positively or negatively, to their management. Multiple managerial identity aspects provide creativity spaces and flexibility in managing conflicts, whilst complex conflict and challenges in conflict management are connected to weakening identity aspects.
Keywords: 650; automotive industry; case study; conflict; identity; identity conflict; South Africa